Multi-center Observational Characterization of Cytomegalovirus Antiviral Use in Allogenic Hematopoietic Stem-cell Transplantation (HCT) Recipients. (4th October 2017) - Musick, William; Vuong, Nancy; Aitken, Samuel L; Liao, Siyun; McManus, Dayna; Cox, James; Perez, Katherine; Tichy, Eric; Topal, Jeffrey; Seropian, Stuart; Danziger, Larry H; Garey, Kevin W
Abstract: Background: No study has recently characterized the real-world incidence of cytomegalovirus (CMV) infection and patterns of CMV antiviral treatment strategies with a focus on toxicities associated with these antivirals in allogeneic HCT recipients in the USA. The purpose of this study was to describe the rates of CMV infection and antiviral treatment patterns from multiple transplant centers in the USA. Methods: This was a three-center, retrospective observational study of allogenic HCT patients from 2006 to 2013. For each patient, data relevant to CMV infection and treatment outcomes were collected with a specific focus on toxicities associated with CMV antivirals (nephrotoxicity, myelosuppression, and electrolyte abnormality). Results: Three hundred and seventeen patients with a total follow-up time of 244, 714 patient-days were included. The most common malignancies requiring HCT were acute leukemia (60.9%), lymphoma (17.7%), and myelodysplastic syndrome (11.4%). CMV infection occurred in 37.5% of patients. Among patients receiving preemptive therapy for cytomegalovirus, valganciclovir was the most commonly used antiviral (76.5%) followed by foscarnet (19.1%), ganciclovir (15.7%), and cidofovir (2.6%). Anemia was the most common toxicity which occurred in 70.4% of patients, followed by thrombocytopenia (45.2%), neutropenia (44.3%), and AKI (29.6%). No relationship was observed between choice of antiviral and the development of neutropenia or nephrotoxicity. Conclusion: A high rate of toxicities associated with anti-CMV antivirals was identified in a large cohort of allogenic HCT patients. Disclosures: All authors: No reported disclosures.